2013
DOI: 10.1038/sc.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome and acute lung injury in patients with vertebral column fracture(s) and spinal cord injury: a nationwide inpatient sample study

Abstract: Study design: Retrospective Nationwide Inpatient Sample (NIS) study. Objectives: To determine national trends in prevalence, risk factors and mortality for vertebral column fracture (VCF) and spinal cord injury (SCI) patients with and without acute respiratory distress syndrome/acute lung injury (ARDS/ALI). Setting: United States of America, 1988 to 2008. Methods: The NIS was utilized to select 284 612 admissions for VCF with and without acute SCI from 1988 to 2008 based on ICD-9-CM. The data were stratified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…In previous studies, inflammatory-associated lung injury was reported to occur following bilateral femur fracture (with fixation) or a vertebral column fracture [26, 38, 39]. However, little information exists regarding adverse effects of the initial traumatic insult and surgical procedures on the lung tissues of aged individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, inflammatory-associated lung injury was reported to occur following bilateral femur fracture (with fixation) or a vertebral column fracture [26, 38, 39]. However, little information exists regarding adverse effects of the initial traumatic insult and surgical procedures on the lung tissues of aged individuals.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Acute SCI patients are certainly at higher risk for ARDS/acute lung injury and death 8 and should be managed with a low tidal volume protocols. Sub-acute SCI patients, however, are generally not felt to be at risk for ARDS and may not need lung-protective ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, SCI induced respiratory dysfunction increases susceptibility to viral pneumonia caused by Covid-19 and likely increased morbidity and mortality compared to their able-bodied counterparts. Furthermore, Veeravagu et al found that persons with SCI are at greater risk of acute respiratory distress syndrome (ARDS) (~95% incidence in critically ill persons with Covid-19) [6]. We suspect that, rather than cough, fever and shortness of breath (typical presenting symptoms in able-bodied persons), hypoxia (<90% SpO2), a worsened ability to clear secretions and tachypnea may be the initial symptoms in persons with SCI.…”
Section: To the Editormentioning
confidence: 99%